LEARNING FROM EXPERIENCE IN THE DURING COVID -19 CHALLENGES AND STRATEGIES IN ONLINE TEEACHING - Vatsiniaina Tatamo Sahondra; Linda Septarina (Proceeding International Conference on Information Technology and Business, 2020)
The coronavirus (COVID-19) during the year 2020 brings challenges for education including transferring online courses. It gives an online experience lecturer to be an inherent advantage over their less tech-savvy counterparts. Online teaching poses challenges and affords opportunities for e-Learning instructors who rely on live communication through types of platforms such as zoom, google meet, and so on. In order to provide materials and lessons explanation. The purpose of this study was to help newcomers overcome the steep learning curve associated with computer-assisted learning. This study mapped the expected benefits, challenges, and strategies for implementing an online e-learning course among teachers with different levels of online teaching experience. The analysis of variance across no- low-, and high-experience groups revealed several findings. Key differences between experience levels were included an expected challenge for instructors and activity choice. an online teaching experience perceived fewer obstacles and used a wider array of communication channels and activities. All groups reported similar levels of expected benefits for instructors, teachers, and challenges for students. The most popular benefits, challenges, strategies, and differences between the no- and high experience groups were discussed and recommendations for future teacher training are given.